On the accuracy of linear DSGE solution methods and the consequences for log-normal asset pricing - Alexander Meyer-Gohde (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2021)
This paper demonstrates a failure of standard, generalized Schur (orQZ) decomposition based solutions methods for linear dynamic stochastic general equilibrium (DSGE) models when there is insufficient eigenvalue separation about the unit circle. The significance of this is demonstrated in a simple production-based asset pricing model with external habit formation. While the exact solution afforded by the simplicity of the model matches post-war US consumption growth and the equity premium, QZ-based numerical solutions miss the later by many annualized percentage points.
Keywords: C61; C63; E17; 330; Numerical accuracy; Production-based asset pricing; DSGE; Solution methods